Spillovers from Japan's Unconventional Monetary Policy to Emerging Asia : a Global VAR approach - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2016)
We use a Global VAR model to study spillovers from the Bank of Japan's quantitative and qualitative easing (QQE) on emerging Asia.1 Our main result is that, despite an appreciation of their currencies vis-a-vis the yen, the impact on emerging Asia's GDP tended to be positive and significant. Our results suggest that the positive effect of QQE on expectations, by improving confidence, more than offset any negative exchange rate spillover due to expenditure switching from domestic demand to Japanese goods. They also suggest that spillovers from QQE might have worked mainly through the impact of expectations and improved confidence, captured by increases in equity prices, rather than through balance sheet adjustments which might have been captured by movements in the monetary base.